Controllable photonic spin hall effect of bilayer graphene. (30th July 2022) - Qi, Song; Da, Haixia
Abstract: Bilayer graphene, composed of two layers of monolayer graphene in AB stacking order, has emerged as an alternative platform for atomically thin plasmonic and optoelectronic devices. However, its behavior of photonic spin hall effect remains largely unexplored. In this work, we have theoretically observed that bilayer graphene has two obvious discontinuities but monolayer graphene only has a single step in the spectra of the spin shifts as a function of wavelength at the Brewster angle over the midinfrared frequency range, which enables a possible route of distinguishing monolayer graphene and bilayer graphene. Additionally, the magnitudes and positions of the peak and valley values in the spectrum of spin shifts of bilayer graphene can be tuned by its Fermi energy. We also achieved the enhanced out-of-pane spin shift of the glass-AB stacking bilayer graphene-air structure at both the Brewster angle ( 33.55 ° ) and the critical angle ( 41.31 ° ) with the aid of the high order of Laguerre–Gaussian beam. The realization of large and controlled spin shift in bilayer graphene indicates its promising applications in precision measurements and refractive index sensors at the midinfrared frequency region.